2006
DOI: 10.1111/j.1469-8137.2006.01650.x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic of the genetic structure of bacterial and fungal communities at different developmental stages of Medicago truncatula Gaertn. cv. Jemalong line J5

Abstract: Summary• The genetic structure of bacterial and fungal communities was characterized in the rhizosphere of Medicago truncatula Gaertn. cv. Jemalong line J5 at five developmental stages (three vegetative and two reproductive stages), and in three compartments (bulk soil, rhizosphere soil and root tissues).• The genetic structure of microbial communities was determined by cultivationindependent methods using directly extracted DNA that was characterized by automated ribosomal intergenic spacer analysis (ARISA).•… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
119
4
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 187 publications
(142 citation statements)
references
References 50 publications
6
119
4
2
Order By: Relevance
“…These data are in agreement with our previous work (24) and underline the gradient of the rhizosphere effect.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…These data are in agreement with our previous work (24) and underline the gradient of the rhizosphere effect.…”
Section: Discussionsupporting
confidence: 83%
“…1). A-RISA DNA fingerprinting was previously shown to be sensitive and robust enough to detect spatiotemporal changes in the genetic structures of the bacterial communities in the rhizosphere of M. truncatula (24).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies suggested that seasonal variations in the activity and relative abundance of rhizosphere bacterial communities are plant-dependent (Dunfield and Germida, 2003;Houlden et al, 2008;Mougel et al, 2006;Smalla et al, 2001). Although some research showed dynamic changes of maize rhizosphere bacterial community at different growth stages using culture-dependent (Cavaglieri et al, 2009;Nacamulli et al, 1997) and fingerprinting methods (Di Cello et al, 1997), detail phylogenetic compositions cannot be monitored due to low resolution of these approaches.…”
Section: Introductionmentioning
confidence: 99%